English Teachers' Perception towards Using ICTs in ELT in Secondary Schools of Bhojpur Municipality: A Census Study - Rai, Uttam Sing (Sahayaatra सहयात्रा, 2023)
This study attempts to investigate English teachers' perception towards using ICTs in English language teaching in Secondary Schools of Bhojpur Municipality. The Census method was adopted to obtain the objectives. Likert-scale survey questionnaires and non-participation observations were adopted as the techniques and tools of data collection to answer the research questions. The result of the study exhibits that the integration of ICTS in teaching English enhances the learning of the English language. The idea of using ICTs such as YouTube videos improves the listening and speaking skills of the English language of both teachers and students. In addition, the majority of English language teachers have a positive attitude towards the use of ICTS in English language teaching. Most of the teachers had positive perceptions towards the use of ICTs in helping students to master their grammatical competence.